Coumarin‐Phosphine‐Based Smart Probes for Tracking Biologically Relevant Metal Complexes: From Theoretical to Biological Investigations. Issue 4 (5th January 2016) - Dondaine, Lucile; Escudero, Daniel; Ali, Moussa; Richard, Philippe; Denat, Franck; Bettaieb, Ali; Le Gendre, Pierre; Paul, Catherine; Jacquemin, Denis; Goze, Christine; Bodio, Ewen
Abstract: Ten metal‐based complexes and associated ligands have been synthesized and characterized. One of the metal ligands is a coumarin‐phosphine derivative, which displays tunable fluorescence properties. The fluorescence is quenched in the case of the free ligand and ruthenium and osmium complexes, whereas it is strong for the gold complexes and phosphonium derivatives. These trends were rationalized by theoretical calculations, which revealed non‐radiative channels involving a dark state for the free ligands that is lower in energy than the emissive state and is responsible for the quenching of fluorescence. For the Ru II and Os II complexes, other non‐radiative channels involving the manifold of singlet and triplet excited states may play a role. The anti‐proliferative properties of all the compounds were evaluated in cancer cell lines (SW480, HCT116, MDA‐MB‐231 and MCF‐7); higher IC50 values were obtained for gold(I) complexes, with the free ligands being only weakly cytotoxic. Abstract : Smart theranostics: Promising coumarin‐based smart probes have been coordinated to Au I, Ru II, Os II and Pt II to evaluate the optical and biological properties of the resulting trackable therapeutic agents. The choice of the metal dramatically impacts the results. The "smart" character of the probe was rationalized by theoretical investigations.